The effect of different light colors on the growth of Nannochloropsis sp. - Nurul Istiqomah; Mukhlis, Alis; Abidin, Zaenal (Generasi Biologi Indonesia, 2024)
The purpose of this study was to determine the effect of different light colours on population density, relative growth and self-replication time in Nannochloropsis sp. This study used a completely randomized design experiment involving 5 treatments and 4 replications. Treatment A uses red light, treatment B uses yellow light, treatment C uses green light, treatment D uses blue light, and treatment E uses white light. Density observations were made every 36 hours. The results of the study showed that differences in the colour of light had a significant effect on population density and relative growth of Nannochloropsis sp. but no significant effect on self-replication time.